PERSEPSI MAHASISWA VOKASI KESEHATAN TERHADAP MULTIPLATFORM DIGITAL PADA KULIAH BAHASA INGGRIS SECARA DARING: HEALTH VOCATIONAL STUDENT'S PERCEPTION OF DIGITAL MULTI-PLATFORM TOWARD ONLINE ENGLISH CLASS - karmilah, Karmilah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2023)
The use of 21st century technology is growing rapidly, especially in the field of education. This is very helpful for online learning that we must use technology, so that students can experience a more meaningful learning experience and can develop their competencies anywhere and anytime. The aim of the research was to obtain information about students' perceptions of the use of digital multiplatform applications during English lectures. online. The applications used include Zoom, G Meet, Google Classroom, Quizizz, Crowd Buzzer, Genially, and you tube. This research method used a qualitative method that focusd on descriptive words. The survey was distributed to 80 odd semester students of the Al Islam Polytechnic of Bandung and interviews with 6 students to clarify the survey that had been filled out and add questions that were not included in the survey. They showd a positive attitude towards using digital multiplatforms during online lectures, even though internet network problems were still an obstacle. Based on interviews with six students. They revealed that the use of digital multiplatforms can help them learn English in an interactive and fun atmosphere.